IMPLEMENTATION OF ELECTRONIC DEVELOPMENT PLANNING DELIBERATION (E-MUSRENBANG) IN COT TRIENG VILLAGE, MUARA SATU DISTRICT, LHOKSEUMAWE CITY - Muhammad Yusuf Baihaki; Muhammad Hasyem; Lisa Iryani; Muklir; Teuku Alfiady (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Electronic Implementation of Development Planning Deliberation in Gampong Cot Trieng, Muara Satu District, Lhokseumawe City is a digital innovation aimed at improving the quality of development planning in the village through community participation and transparency based on information technology. However, in practice, this system has not run optimally. This study aims to describe the implementation of E-Musrenbang in Gampong Cot Trieng, Muara Satu District, as seen through community participation, information transparency, and effectiveness. This study uses a qualitative approach using primary and secondary data sources with data collection techniques through observation, interviews and documentation. This study was analyzed using George C. Edwards III's policy implementation theory which includes four main variables: communication, resources, implementer disposition, and bureaucratic structure. The results of the study indicate that in terms of participation, the community has not been directly involved due to limited access to the system. In terms of transparency, there is no open information regarding Musrenbang proposals and results. Meanwhile, in terms of effectiveness, the shift from manual to digital systems shows positive progress, but the overall utilization of the system still needs to be improved. These obstacles are reinforced by weak communication, limited infrastructure and human resources, the commitment of village officials is good but still constrained by technical and team support, and the bureaucratic structure that supports the system in an integrated manner is not yet optimal. Improvement efforts are needed in various aspects so that the implementation of E-Musrenbang can truly encourage participatory, transparent and effective development planning.